Autofagi : Mekanisme Pemeliharaan Diri Sel dalam Kondisi Stres - Kanisia Petra Seto Lejo; Jihan Pramitha Kanggo; Maria Ventiana Wea; Alfa Zaki; Veronika P. Sinta Mbia Wae (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Autophagy is a cellular mechanism in the form of degradation and recycling of intracellular components that plays an important role in maintaining cell homeostasis, especially when cells are under stress conditions such as nutritional limitations, oxidative stress, organelle damage, or pathogen attacks. Through this process, cells are able to survive by eliminating damaged or dysfunctional structures, while simultaneously reusing the degradation products as a source of energy and building blocks for new molecules. This study aims to examine the mechanism of autophagy, the molecular regulations involved, and its role in the response to various forms of cellular stress using a literature review method. Reference sources in this study come from relevant scientific articles and are accessed through PubMed, Scopus, and Google Scholar databases with a publication year range of 2015-2024. Articles are selected based on the main inclusion criteria, namely discussions on the molecular pathway of autophagy, the process of autophagosome formation, and the role of lysosomes in cellular degradation mechanisms. The study results indicate that autophagy is an essential adaptive mechanism primarily controlled by the mTOR and AMPK pathways in response to cellular stress. Adaptive autophagy plays a crucial role in maintaining cell stability and survival, while autophagy dysfunction or uncontrolled activation is pathological and contributes to the development of various diseases, making autophagy a strategic therapeutic target. Furthermore, disruption of the autophagy process is known to be closely associated with the development of various degenerative and metabolic diseases, making autophagy a potential target in the development of biomedical therapeutic strategies.